INSTITUTE OF MANAGERS OF EDUCATIONAL PROGRAMS OF THE JUDICIARY, IMPROVE THE EFFICIENCY OF SCIENTIFIC RESEARCH AND MANAGEMENT TRAINING (FOR EXAMPLE, SOUTHERN FEDERAL UNIVERSITY) - Tatiana Anopchenko (Вестник Северо-Кавказского федерального университета)
In the modern world the understanding that it is necessary to make efforts on modernization of education for improvement of its quality was strongly approved. There was a need for development of the new educational policy adequate to features of a modern economic environment. Former priorities were succeeded by other forms offunctioning and regulation of the higher education. It is undoubted that during an era of development of Internet technologies use of new institutes is a determinant of development of society and therefore in the modern world the tendency to merge of educational structures, integration ofrequirements to quality ofresults of education, formation of the new educational integrated technologies of training takes place. All this is possible through institute of heads of educational programs. In article experience of creation and advance of institute of heads of educational programs on the basis of the Southern federal university is considered.